Strategi Bauran Pemasaran Motor Yamaha dengan Analisis SWOT pada Dealer Armada Pagora Jaya Tulungagung - Dadang Setyawan (Jurnal Simki Economic, 2019)
This research is motivated by intense competition, both with different brands or with one brand. So dealers need to recognize the strengths and weaknesses of the business and know the opportunities and threats that can affect business activities. By evaluating the company's internal and external factors, it will greatly assist the company in recognizing itself, and can be used to develop strategies to increase sales levels. The purpose of this study is to determine the company's internal and external factors that will be used to create a strategy to increase sales of Yamaha motorcycles at the Pagora Jaya Tulungagung Fleet dealer. This research uses qualitative and quantitative approaches with descriptive techniques. Qualitative approach to explain the problem of looking for a rating to be used in the SWOT matrix. A quantitative approach is used to calculate the SWOT matrix. Pagora Jaya Tulungagung Fleet Dealer is in quadrant I (one), namely in the Growth position. With the results of a score of 3.96 strengths, 2.86 weaknesses, 2.36 opportunities and 1.7 threats. In this position the Pagora Jaya Tulungagung Fleet dealer can increase product competitiveness by adding product marketing branches and adding product innovation